EP1088 Pelvic leiomyomatosis (about a case and literature review). (1st November 2019) - Serraj, M; Assal, A; Baroud, O; Benhessou, M; Ennachit, M; El Karroumi, M
Abstract : Introduction/Background: The Pelvic Leiomyomatosis a benign disease, rare, characterized by the proliferation of various nodules in smooth muscle cells in the peritoneal cavity, which usually affects young women of childbearing age. Methodology: We report a case of disseminated peritoneal leiomyomatosis in a woman aged of 40 years old, nulligeste and nulliparous, who had never used oral contraceptives, suffering from chronic pelvic pain with abdominal-pelvic mass, she had undergone a subtotal hysterectomy because of myomatous uterus by laparotomy way, the various radiological studies have found a parietal mass in the right lower quadrant with tissular density, a large mass in retro and sus vesicle, some peritoneal pelvic nodules and a nodule under the skin in front of the pubic symphysis. The patient had an exploratory laparotomy with resection of the parietal mass, the histological examination showed a much limited cellular leiomyomas. Results: The evolution was characterized four months later by a parietal recurrence and development of multiple nodules in the peritoneal cavity, the patient had a second laparotomy with resection of the graft nodules on the paries, the peritoneum and the digestive structures, histological examination showed a leiomyomatosis without malignancy. The patient used analogues GnRH during 1 year with poor supervision of the treatment, and had been lost to sight despite repeated attempts to contact her. Conclusion: The definite diagnosis is histological. The evolution is generally favorable. The malignant transformation in a leiomyosarcoma is rare but its prognosis is catastrophic. When a hormonal factor is recognized, the stop of the estrogen exposures allows the regression of the disseminated peritoneal leiomyomatosis in the majority of the cases. Some cases will require more expensive management. The extreme gravity of the prognosis in the cases of sarcomatous change requires the utmost vigilance in the supervision of the patients. Disclosure: Nothing to disclose